Systematic identification of lincRNA‐based prognostic biomarkers by integrating lincRNA expression and copy number variation in lung adenocarcinoma - Wang, Li; Zhao, Hongying; Xu, Yingqi; Li, Jing; Deng, Chunyu; Deng, Yulan; Bai, Jing; Li, Xia; Xiao, Yun; Zhang, Yunpeng (International journal of cancer, 2019)
Copy number alterations (CNAs) of lincRNAs act as one of important mechanisms in disrupting lincRNA expression which may play critical roles during tumorigenesis in lung adenocarcinoma (LUAD). The copy number alterations of lincRNAs can mark the spectrum of cancer progression and may serve as biomarkers for prognosis in LUAD, however it is rarely studied. We analyzed RNASeq data for 488 LUAD patients from TCGA portal and 58 healthy subjects to identify prognostic lincRNAs predictive of patient survival. Computational analysis entailing integration of expression and copy number alteration data revealed five prognostic lincRNAs: RBPMS‐AS1, TDRKH‐AS1, LINC00578, RP11‐470 M17.2 and LINC00941. The copy number alterations in the LINC00578 and RP11‐470 M17.2 genes were positively associated with the longer overall survival of LUAD patients. The CNA in LINC00941 was negatively associated with the longer overall survival. Copy number amplification significantly correlated with increased expression of TDRKH‐AS1, which regulates telomere organization and EZH2‐mediated epigenetic silencing of CDKN1A, CDKN1B and IL24. Decreased survival of LUAD patients was associated with high LINC00941 expression. The LINC00941 regulates the PI3K‐AKT signaling pathway, focal adhesion by influencing potential targets, such as KRAS proto‐oncogene GTPase and VEGFC. These lincRNA‐based prognostic biomarkers may destroy important cancer‐related biological processes contributing to LUAD prognosis. In summary, we demonstrate the prognostic potential of four differentially expressed lincRNAs with copy number alterations (RBPMS‐AS1, TDRKH‐AS1, LINC00578 and RP11‐470 M17.2) that are positively associated with longer overall survival of LUAD patients. One differentially expressed lincRNA LINC00941 with copy number alterations was negatively associated with longer overall survival of LUAD patients. What's new? Changes in gene copy number are among the most frequent genetic anomalies occurring in human cancers. The relevance of copy number alterations (CNAs) that occur in noncoding regions, however, remains unclear. Here, investigation of CNAs in long intergenic noncoding RNAs (lincRNAs) in lung adenocarcinoma patients led to the identification of five prognostic lincRNAs. Elevated expression of one of the genes, LINC00941, which regulates PI3K‐AKT signaling and focal adhesion, was negatively associated with lung adenocarcinoma survival. The other four lincRNAs were positively associated with lengthened overall survival. The lincRNA TDRKH‐AS1 contributed to prognosis via regulation of mitochondrial activity and telomere organization.